Epimerization and chain scission of polylactides in the presence of an organic base, TBD. (November 2020) - Meimoun, Julie; Favrelle-Huret, Audrey; Bria, Marc; Merle, Nicolas; Stoclet, Grégory; De Winter, Julien; Mincheva, Rosica; Raquez, Jean-Marie; Zinck, Philippe
Abstract: The epimerization of polylactide is reported in the presence of 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) at 105 °C in toluene. The extent of the reaction depends on the amount of TBD introduced and the reaction time. Up to ca. 46% D units can be formed starting from poly(l -lactide) in the presence of 5 mol% TBD. The epimerization rate is slightly higher for D-stereoisomers vs. L-stereoisomers. From the decrease of the number-average molecular weight observed, a concomitant chain scission reaction is observed. A possible mechanism based on a nucleophilic attack of TBD is proposed based on NMR analyses, notably DOSY, MALDI ToF mass spectrometry and IR spectroscopy. The implications of the work in the field of polymer synthesis and chemical recycling of polylactide are discussed. Highlights: Poly(l -lactide) and poly(d -lactide) are epimerized to up to 46% with TBD. The epimerization rate is slightly higher for D stereoisomers vs. L stereoisomers. A chain scission reaction is evidenced. A mechanism based on a nucleophilic attack of the base is proposed.